A Consideration of the Relationship Between Music and Collective Identity: From the Viewpoint of Cultural Psychology of Music - Ana Đorđević (University of Belgrade, 2020)
The aim of the present study lies in an effort of converging anthropological, ethnomusicological and psychological approach to the relationship between music and collective identity. Music is considered a socio-cultural artifact, which mediates the processes of collective identity construction, and whose function in such process can be multiple. In order to understand the ways in which it is sutured into (in)formal processes of collective (self)identification, we propose simultaneous consideration of various dimensions: cultural, social, political, psychological. Although there already has been interdisciplinary research of the role of music in the emergence of identity, we advocate for a more complementary approach, by a consideration of the psychological accounts, adjusted to the needs of ethno-anthropological analysis. As the most comprehensive theoretical approach, we propose cultural psychology of music. Future empirical research on specific identity processes mediation by music as cultural artifact, should include the analysis of intersecting local and global social trends, aspects of musicological analysis, specificities of psychological development of identity, the role of socio-political strategies of identity formation, and, last but not least, cultural specificity of the community in focus of the research. We find the complexity of the phenomenon in focus to be obligatory for the complexity of the theoretical and methodological approach.